Enhancing diabetes therapy adherence: a comprehensive study on glucometer usability for type 2 diabetes patients - Toletti, Giovanni; Boaretto, Andrea; Di Loreto, Chiara; Fornengo, Riccardo; Gigante, Alfonso; Perrone, Giovanni (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundSelf-monitoring of blood glucose (SMBG) is a vital practice for type 2 diabetes (T2DM), and glucometers have the potential to improve therapy adherence. However, characteristics of glucometers improving their usability are underexplored. A knowledge gap exists regarding patients under 65, warranting further research for diabetes care improvement. Thus, this study aims to gather insights on glucometer accessibility, by analyzing the case of the Accu-Chek® Instant glucometer by Roche Diabetes Care GmbH.MethodsStarting from a previous study having the objective of investigating devices’ features able to improve SMBG in over 65 T2DM patients, using the same device, we enlarged the scale, designing a survey that collected answers from 1145 patients of the Center and South of Italy, both under and over 65. 957 answers were analyzed, according to a threshold of 50% completion of the answers.ResultsOur results show the major characteristics presented in Accu-Chek® Instant are appreciated differently between patients under 65 and over 65, and between patients with or without previous experience with a glucometer.Discussions and conclusionsIt emerged how Accu-Chek® was perceived as more user-friendly among individuals under 65 compared to those aged 65 and over, where more people had prior experience, indicating how such a glucometer can be particularly helpful for naive patients. The study provides valuable insights to the academic discourse on glucometer features and their influence on therapy adherence.